Klasifikasi Batuan Perangkap Aspal Batu Buton (Asbuton) Berdasarkan Analisis Geokimia di Desa Winning, Kecamatan Pasarwajo, Kabupaten Buton, Provinsi Sulawesi Tenggara - Isman Saleh; Amritzal Nur Firdaus (OPHIOLITE: Jurnal Geologi Terapan, 2024)
This research is located in the IUP area of PT Wijaya Karya Bitumen, C Block Kabungka Mine, Winning Village, Pasarwajo District, Buton Regency, Southeast Sulawesi Province. This study aims to classify asbuton trap rocks based on their chemical composition with XRF (X-ray fluorescence) and XRD (X-Ray Diffraction) analysis. The results of the XRF analysis showed that the asbuton trap rocks in the research area were dominated by CaO, MgO and SiO2 compounds. The CaO content varies between 24.56% to 44.46%. The SiO2 content in the samples varies, ranging from 7.81% to 12.54%. Three samples, namely TR1C-001, TR1C-002, TR1C-003 each contain MgO 0.57%, 0.85%, and 0.96%, while the other two samples, namely TR2C-001, TR2C-002 each contain MgO 14.40% and 17.51%, respectively. The results of XRD analysis showed three dominant minerals, namely Calcite (CaCO3), Quartz (SiO2) and Dolomite (CaMg(CO3)2). Based on the results of geochemical analysis (XRF and XRD) showed that the asbuton trap rock in the study area consists of 2 (two) types of carbonate rocks, namely Argillaceous Limestone with a CaCO3 content of 76.6% to 79.7% and slightly calcitic dolomite.